Uji Validitas dan Reliabilitas Dalam Edukasi Agama Islam Untuk Anak Usia Dini Melalui Film Rara dan Nussa di Era Digital Dengan Software SPSS - Friska Aryanti; Qhintara F. P. Wahyono; Calyca D. Araminta; Lusia K. Jannah; Erwin Kusumastuti (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
In the rapidly evolving era of technology, the need for innovative and effective Islamic education for young children is becoming increasingly pressing. Therefore, this research aims to explore the effectiveness of the film "Rara and Nussa" as a means of Islamic education for young children in the digital age. Against the backdrop of changing dynamics of life and the need for innovation in Islamic education, this research presents an analysis related to the validity and reliability of the research instrument as well as the effectiveness of the film. Through data collection using questionnaires distributed to 50 respondents, and analysis using SPSS software, the research findings indicate that the film "Rara and Nussa" has a strong correlation with understanding Islamic values, reinforces moral values, and enhances the quality of Islamic education. Statistical analysis results show high correlation values and convincing significance, as well as instrument reliability that can be trusted. This conclusion confirms that the use of appropriate research methods and accurate data analysis can strengthen research findings regarding the effectiveness of films as a means of Islamic education for young children, providing a significant contribution to the development of Islamic education in the digital era.